2002
DOI: 10.1590/1809-43922002322240
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of leaf Nitrogen content in trees of Amazonian floodplains

Abstract: -In Amazonian floodplains the trees are exposed to extreme flooding of up to 230 days a year. Waterlogging of the roots and stems affects growth and metabolic activity of the trees. An increased leaf fall in the aquatic period and annual increment rings in the wood indicate periodical growth reductions. The present study aims at documenting seasonal changes of content. Leaves of six tree species common in floodplains in Central Amazonia and typical representants of different growth strategies were collected ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…Leaf N content of species in the Mapire igapó (Rosales, 1988) was similar to that in the Rio Negro igapó (Parolin et al, 2002), with an average of 2% (by dry mass). No data are available for seasonal variations in leaf N content in the Mapire igapó; in the Rio Negro igapó, content varied between the drained and the flooded phases, with no consistent trend, since in some species content decreased, whereas in others it increased with flooding.…”
Section: Models Of Physiological Responses To the Inhibitory And The supporting
confidence: 54%
“…Leaf N content of species in the Mapire igapó (Rosales, 1988) was similar to that in the Rio Negro igapó (Parolin et al, 2002), with an average of 2% (by dry mass). No data are available for seasonal variations in leaf N content in the Mapire igapó; in the Rio Negro igapó, content varied between the drained and the flooded phases, with no consistent trend, since in some species content decreased, whereas in others it increased with flooding.…”
Section: Models Of Physiological Responses To the Inhibitory And The supporting
confidence: 54%
“…The availability of large databases for plant traits [Kattge et al, 2011] provided a unique opportunity to include leaf nitrogen content data in the LUE opt prediction model. Leaf traits such as leaf nitrogen content and SLA can be temporally dynamic in response to seasonal canopy changes, stand age, and disturbance recovery [Parolin et al, 2002;Nouvellon et al, 2010], affecting canopy photosynthetic capacity, light use efficiency, and GPP, and others have shown that canopy N can explain a substantial amount of variation in productivity from minute to year scales [Kergoat et al, 2008;Ollinger et al, 2008;Reich, 2012]. Our investigation focus was on estimating spatial patterns in LUE opt using limited ground observations of general leaf traits, while the effects of temporal leaf trait variations on LUE opt and associated GPP calculations were not explicitly represented and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf size decreases under nutrient-poor conditions or when water is limiting (Westoby et al 2002). In wet conditions, there is little research on the effects of oxygen supply on leaf size, and leaf size responses seem to be species dependent (Angelov et al 1996;Parolin 2002;Glenz et al 2006). Probably, the effects of oxygen stress on leaf size are indirect through negative effects on nutrient supply.…”
Section: Sems Of Plant Strategies In Relation To Nutrient Availabilitmentioning
confidence: 99%